Da fotografia na cidade a cidade na fotografia: Ribeirão Preto 1891-1923 - Marques, Higina Teixeira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work intends to analyze some aspects of the production and diffusion of photografic images in Ribeirão Preto, correlating them to the urban development of this coffee producer city. The historical moment proposed (1891-1923) takes into account the urban interventions driven by the expansion of coffee culture, the contact with the new techniques which arose from this experience, the peformance of some photographers in the city and the publication of photo portfolios, periodicals and magazines created to disseminate the transformations occured in the urban area.When mapping aspects of production and circulation of photografic images, one of the remarkable features of modern societies, we also expect to recover important elements of the historicity of the local perception. The quantitative and qualitative analysis of published photos seeked to identify recurring patterns regarding the motifs and characteristic manners of these images, important elements for the construction of the visuality of the city, associated to the imagery of urban modernity

Este trabalho tem como objetivo analisar alguns aspectos da produção e da divulgação de imagens fotográficas em Ribeirão Preto, correlacionando-os ao desenvolvimento urbano deste centro produtor de café. O recorte histórico proposto (1891-1923) considera o auge das intervenções urbanas motivadas pela expansão da cultura cafeeira, o contato com as novas técnicas decorrentes dessa experiência, a atuação de alguns fotógrafos na cidade e a publicação de álbuns fotográficos, almanaques e revistas elaborados para divulgar as transformações ocorridas no meio urbano. Ao mapearmos aspectos da produção e circulação de imagens fotográficas, um dos traços marcantes das sociedades modernas, esperamos recuperar também importantes elementos da historicidade da percepção local. A análise quantitativa e qualitativa de fotografias publicadas buscou identificar padrões de recorrência quanto aos motivos fotografados e as formas características destas imagens, elementos importantes na construção da visualidade da cidade associada ao imaginário da modernidade urbana
Keywords: História; Imagens fotograficas; Fotografia documentaria - São Paulo (Estado); Sociologia historica; Evolução social; Ribeirão Preto (SP) - História